Millennium Development Goals (MDGS) in Nigeria: Issues and Problems (Global Journal of Human-Social Science, 2014)
Development is a key factor in every given society. Although, the concept of development and its understanding differs from society to society. That is, each society has ways of developing itself passing through the necessary developmental stages. The success of these stages is a function of many key factors such as the environment, interaction with other societies within and outside, leadership and its style, management, culture, individual and collective goal(s) of the people and of the community and the people themselves. The MDGs is meant for Africa as a continent with a bench mark of 2015, what is the situation of realization of these goals in spite of the financial resources committed to this course ? What are measures put in place by Nigeria as a country or to what extent have we gone in realizing these MDGs? Hence this article to investigate the issues and problems of MDGs in Nigeria. The secondary method of data collection was thoroughly explored in this article. The article noticed that Nigeria as the GIANT of Africa might not attain the MDGs even if smaller nations (Ghana, Cameroon and Botswana etc) in Africa does.